Utilization of Imaging to Identify a Benign Condition Mimicking Acute Appendicitis in a Child. (August 2018) - Phalke, Neelam; Mehta, Zubin; Das, Samrat
One of the most concerning causes of abdominal pain affecting children is acute appendicitis. However, there are benign conditions that can closely mimic appendicitis in children. In this article, we present a case of a child admitted for possible acute appendicitis and determined to have a condition known as omental infarction. The patient was managed medically and made a full recovery without surgical intervention. The aim of this case report is to review omental infarction and present a way of differentiating this disease from appendicitis, utilizing imaging, with the goal of avoiding surgical intervention. We also discuss the presentation and imaging findings of and another closely related condition—epiploic appendagitis. It is important to differentiate appendicitis from these 2 conditions as they can be often managed medically without surgical intervention.